Aesthetic Consciousness and Literature: Sartre’s Existential Queries (Literary Voice, 2025)
Jean-Paul Sartre raised a number of pertinent existential questions exploring the realms of not just art, philosophy and literature, but addressed all aspects of man’s being. His philosophic thought starts with two types of being- Being-in-itself and Being-for-itself. In-itself is the transcendent essence of human existence, therefore beyond the framework of space and time. Being-for-itself perpetually seeks completion. Being arises through Nothingness, yet Nothingness denies Being. He discusses three types of consciousness: perceptual, conceptual and imaginative. Imagination functions on the basis of the negation of what is here and now. The imaginative act results in the creation of an unreal object. Why then does man create art? This is the question which immediately arises in this context. All creative activity, according to him, derives its impetus from Being-for-others. Art is an expression language (the term 'language' here is taken in a wider sense and does not merely refer to verbal language) that reveals the others. Without language, no awareness is possible- of oneself as well as of others. Therefore, language becomes valuable as a means of revealing the other in his essential freedom. His essay ‘What is Literature?’ delves into the deeper queries of the creation of literature, beginning with what, for whom, what should and so on.
Keywords: Aesthetics, consciousness, existentialism, Jean-Paul Sartre, literature, language.